MUSLIM TEACHERS WORKING IN CHRISTIAN SCHOOLS: A PORTRAIT OF RELIGIOUS MODERATION IN MAKASSAR - St. Aflahah; AM Saifullah Aldeia; Khaerun Nisa (Khazanah: Jurnal Studi Islam dan Humaniora, 2022)
Faith-based schools are still debated since it does not teach students pluralism. While in Indonesia, such schools are growing rapidly due to parents' concern about the minimal time for religious study in public schools. In Makassar, Islamic schools are the most significant number, but certain Muslim teachers decide to work in Christian schools. This study focused on exploring their reasons and connecting them to the concept of Religious Moderation issued by The Indonesian Ministry of Religious Affairs. As a qualitative descriptive, this research used a semi-structured interview method to describe the participants' experiences in-depth. The two of four indicators of Religious Moderation, tolerance and national commitment, are the framework for discussing the implementation of Religious Moderation in the schools. The results show that Muslim teachers work in Christian schools because of nothing against Islam, high salary, and teacher capacity building. Moreover, while teaching at this school, participants found their Muslim identities are identified through their Arabic names. However, it does not affect their teaching professionalism. A harmonious relationship is shown between Muslim teachers and Christian students and between Muslim and Christian teachers. They represent a religious tolerance, including allowing Muslim teachers to perform Friday prayers and wishing Christian students and teachers a Merry Christmas. Furthermore, Muslim teachers indicate a national commitment by teaching students professionally regardless of religion as regulated in the basic national consensus of Indonesia, Pancasila. Thus, this faith-based school is critical in supporting the concept of Religious Moderation and plurality in Indonesia